The Influence of Export Price and United States Gross Domestic Product (GDP) toward Export Volume of Central Java Plywood to United States - Anida - Nikmatika; Achmad - Zaenuddin; Azizah - Azizah (JOBS (Jurnal Of Business Studies), 2021)
The volume of Central Java plywood exports to the United States fluctuated with the highest decline occurring in 2016 of 46,999,336 kg. The state of fluctuating export volume is not balanced with the United States' GDP which increases every year. There are several factors that affect the amount of plywood exports, namely the GDP of the destination country and the export price. The aim of this research is to analyze the influence of export price and United States GDP toward central java plywood export to United States both simultaneously and partially. This research is an explanatory research with quantitative approach. Multiple Linear Regression Analysis method is used in this research equipped with the Descriptive Statistics Test, Classic Assumption Test, Multiple Linear Regression, Coefficient of Determination, F-Test and t-Test. Data used in this study are secondary data which are obtained by doing a documentary study. The result of t-Test shows that Export Price there is no significant and positive influence on Central Java plywood Export Volume to United States, meanwhile United States GDP have significant and positive influence on Central Java plywood Export Volume to United States. The result of F-Test shows that Export Price and United States GDP simultaneously influence on Central Java plywood Export Volume to United States. Based on determination coefficient, export price and US GDP have an influence on Central Java plywood Export Volume to United States by 30.8%. Meanwhile, the remaining 69.2% was explained by another variable that was not examined in this study